1992
DOI: 10.1063/1.351200
|View full text |Cite
|
Sign up to set email alerts
|

Annealing studies of low-temperature-grown GaAs:Be

Abstract: An approximate continuum theory for interaction between dislocation and inhomogeneity of any shape and properties J. Appl. Phys. 109, 113529 (2011) Direct comparison of boron, phosphorus, and aluminum gettering of iron in crystalline silicon J. Appl. Phys. 109, 073521 (2011) Impact of type of crystal defects in multicrystalline Si on electrical properties and interaction with impurities J. Appl. Phys. 109, 033504 (2011) Low-temperature acoustic properties of nanostructured zirconium obtained by intensive pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 24 publications
1
43
1
Order By: Relevance
“…This is in accordance to the assumptions in the earlier PAS studies. [9][10][11]40,49 Due to the combination of different techniques in conjunction with theoretical calculations in the present study, the identification of V Ga can now be considered to be well established. Positron lifetime spectroscopy showed that the defects are monovacancies, whereas the conventional S -W analysis shows that they belong to the Ga sublattice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is in accordance to the assumptions in the earlier PAS studies. [9][10][11]40,49 Due to the combination of different techniques in conjunction with theoretical calculations in the present study, the identification of V Ga can now be considered to be well established. Positron lifetime spectroscopy showed that the defects are monovacancies, whereas the conventional S -W analysis shows that they belong to the Ga sublattice.…”
Section: Discussionmentioning
confidence: 97%
“…The formation of As precipitates has often been explained in terms of a V Ga mediated diffusion of As Ga antisites. 9,19 Positron annihilation results indicate the formation of defects larger than monovacancies during annealing. 10,11 It has been suggested that positron trapping in annealed LT-GaAs is related to As precipitates 20 whereas other authors interpreted their results in terms of isolated vacancy clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the technological potential of LT-MBE GaAs, a lot of work has been performed on understanding the defects in this material [59,60,61,64,65,66,67]. In contrast only a few reports have been published on gallium nitride grown at low temperature [68,69].…”
Section: Lt-mbe Grown Ganmentioning
confidence: 99%
“…At that temperature the full width at half maximum of the rocking curve is the smallest for all three Be concentrations used in the experiments. At larger annealing temperatures, the lattice mismatch appears again, most probably, due to the increase of Be impurity mobility and their activation as acceptors [12]. Because Be atoms in LTG GaAs layers are substitutional, they prevent vacancy assisted diffusion of As into precipitates and stabilize As Ga defects.…”
Section: Growth and Structural Characterization Of Be-doped Ltg Gaasmentioning
confidence: 99%